A Social Capital In Contemporary Indonesia: Examining Faith-Inspired Civil Society and Democracy - Zaenuddin, Dundin; Maunati, Yekti; Ardhana, I Ketut; Sofjan, Dicky (Religió Jurnal Studi Agama-agama, 2022)
As a national agenda for development, democracy needs to be developed and deepened by both the Indonesian state and society to achieve a just and prosperous country. Within this framework, faith-inspired civil society organizations are expected to promote equality before the law and observe humanistic, pluralistic and tolerant religious social life. This study employs the theory of Bourdieu’s Habitus, Gellner’s Typology of Social Organization and Kymlicka’s Multicultural Citizenship. It also engages other sociological theories, namely the social capital theory of civic community from Putnam, Coleman, Uphof, and religion-state relations theory from Bolland, Menchik, and Hassan. This study is qualitative with a multidisciplinary approach derived from Sociology, Anthropology, Political Science, and History. Research findings suggestthe following: (1) The imbalance of bonding and bridging social capital has tended to result in hegemonic relations among faith-inspired civil society that to some extent excludes equal participation of ‘the others’; (2) The social capital of civil society organizations is highly nuanced and formed based on differences in religious and political orientations, which are the resultant interpretation and understanding of the Sacred texts and its religious culture; (3) Nahdlatul Ulama, Muhammadiyah and Persatuan Tarbiyah Indonesia with moderate religious orientations (wasatiyah) have contributed positively to social capital that is persistent and consistent with democracy, while Hizbut Tahrir Indonesia (HTI) and Front Pembela Islam (FPI) and to a lesser extent Gereja Masehi Injili di Minahasa (GMIM) with religious fundamentalist outlook tend to have an imbalanced social capital, which is resistant toward the so-called “Pancasila democracy”.